2007
DOI: 10.1007/s10689-007-9117-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences regarding recontact by cancer genetics clinicians

Abstract: Patients evaluated in a colon cancer risk assessment clinic want updated information at a rate similar to those who participated in a colon cancer gene testing study. These findings have implications for the consultative nonlongitudinal nature of such clinics and suggest patient preferences for personally-tailored information could be labor intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
7
20
1
Order By: Relevance
“…It was argued that recontacting could prevent professionals from being held liable for negligence by former patients, who might claim a need to know any new, medically relevant information. 1,5,15,28,59 The opposite issue-that patients could sue their HCP because recontacting breached their right not to know-was not explicitly addressed in the literature, although the importance of a patient's right not to know was often mentioned. Liability was, however, discussed as a counterargument by Letendre and Godard,20 reasoning that professionals may make themselves vulnerable if they cannot satisfy the expectations raised by embracing a recontacting policy.…”
Section: Elsi Issues Regarding the Duty To Recontactmentioning
confidence: 99%
See 2 more Smart Citations
“…It was argued that recontacting could prevent professionals from being held liable for negligence by former patients, who might claim a need to know any new, medically relevant information. 1,5,15,28,59 The opposite issue-that patients could sue their HCP because recontacting breached their right not to know-was not explicitly addressed in the literature, although the importance of a patient's right not to know was often mentioned. Liability was, however, discussed as a counterargument by Letendre and Godard,20 reasoning that professionals may make themselves vulnerable if they cannot satisfy the expectations raised by embracing a recontacting policy.…”
Section: Elsi Issues Regarding the Duty To Recontactmentioning
confidence: 99%
“…9,30 The other six articles presented data from surveys and focus groups about the implementation of recontacting from the perspective of both counselors and patients. 12,14,25,28,49,59 These studies described opinions on recontacting as part of standard care; possible benefits, burdens and methods; and professional opinions about using genetic registries for recontacting patients. These data showed that opinions of professionals and patients generally differed on who is responsible for recontacting and on the ethical principles of recontacting.…”
Section: Empirical Evidence On the Duty To Recontactmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been written about the duty to recontact, with very little consensus reached on the specifics of how and when to do so. 12,13 Most research agrees that, in theory, recontacting patients and providers with updated information is optimal; however, the process by which this should occur is not agreed on. 14 These complications argue that minimizing the need to recontact by providing accurate and complete information as early as possible is the best practice.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of ''recontacting'': the re-establishing of contact with patients on the basis of new information derived from a stored genome sequence. This recontacting can be done either on the initiative of the doctor, or that of the patient [37]. A typical scenario involves unsolicited information and the patient being unaware of a purported genetic threat of some sort.…”
Section: Shifting Normative Frameworkmentioning
confidence: 99%